Effects of carbohydrate drinks ingestion on executive function in athletes: a systematic review and meta-analysis - Yang, Jingye; Han, Qi; Liu, Qi; Li, Tieying; Shao, Yongcong; Sui, Xuemei; Wang, Qirong (Frontiers in Psychology, 2023)
Background: Carbohydrates are often used as boosters for endurance and high-intensity exercise. However, it is unclear whether carbohydrate drinks intake before or during exercise can affect specific domains of cognitive function, such as Executive Function (EF). Methods: Following the guidance of PRISMA 2020, we searched six major databases including PubMed, WOS, SPORTDiscus, Cochrane, Embase, and Scopus. Outcomes were presented in the form of Reaction Time (RT), Accuracy (ACC), and Scores (Score) for performing EF tests. Effect sizes were calculated from the test results of EF and expressed as standardized mean differences (SMDs). After analyzing the overall results, we performed subgroup analyses based on the athletes' program characteristics. Results: After retrieving a total of 5355 articles, ten randomized controlled trials (RCTs) were identified and included in this review. The overall results showed that the intake of carbohydrate drinks before or during exercise did not have a significant effect on the reduction of EF after exercise (ACC (-0.05 [-0.27, 0.18]); RT (-0.18 [-0.45, 0.09]); Score (0.24 [-0.20, 0.68])). The subgroup analyses based on open skill sports and close skill sports also showed invalid results, but the results of RT ended up with different preference (ACC of open skill sports athletes (-0.10 [-0.34, 0.14]); RT of open skill athletes (-0.27 [-0.60, 0.07]); RT of close skill athletes (0.29 [-0.24, 0.82])) Conclusions: The intake of 6%-12% of single or mixed carbohydrates before or during exercise was not significantly effective in reducing the decline in EF after exercise. Our findings may have been influenced by the type of intervention, dose, mode of administration, or individual variability of the included subjects.